Nitrogen cycling in canopy soils of tropical montane forests responds rapidly to indirect N and P fertilization. (25th July 2014) - Matson, Amanda L.; Corre, Marife D.; Veldkamp, Edzo
Abstract Although the canopy can play an important role in forest nutrient cycles, canopy‐based processes are often overlooked in studies on nutrient deposition. In areas of nitrogen (N) and phosphorus (P) deposition, canopy soils may retain a significant proportion of atmospheric inputs, and also receive indirect enrichment through root uptake followed by throughfall or recycling of plant litter in the canopy. We measured net and gross rates of N cycling in canopy soils of tropical montane forests along an elevation gradient and assessed indirect effects of elevated nutrient inputs to the forest floor. Net N cycling rates were measured using the buried bag method. Gross N cycling rates were measured using 15N pool dilution techniques. Measurements took place in the field, in the wet and dry season, using intact cores of canopy soil from three elevations (1000, 2000 and 3000 m). The forest floor had been fertilized biannually with moderate amounts of N and P for 4 years; treatments included control, N, P, and N + P. In control plots, gross rates of NH4+ transformations decreased with increasing elevation; gross rates of NO3− transformations did not exhibit a clear elevation trend, but were significantly affected by season. Nutrient‐addition effects were different at each elevation, but combined N + P generally increased N cycling rates at all elevations. Results showed that canopy soils could be a significant N source for epiphytes as well as contributing up to 23% of total (canopy + forest floor) mineral N production in our forests. In contrast to theories that canopy soils are decoupled from nutrient cycling in forest floor soil, N cycling in our canopy soils was sensitive to slight changes in forest floor nutrient availability. Long‐term atmospheric N and P deposition may lead to increased N cycling, but also increased mineral N losses from the canopy soil system.